Internet censorship detected in Russia (Russia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Russia. Data sourced from CensoredPlanet.
Censorship Incident ID: RU-2026-0530. Severity: critical. Confidence: 65%